2018
DOI: 10.1101/275222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weakly-bound Dimers that Underlie the Crystal Nucleation Precursors in Lysozyme Solutions

Abstract: Protein crystallization is central to understanding of molecular structure in biology, a vital part of processes in the pharmaceutical industry, and a crucial component of numerous disease pathologies. Crystallization starts with nucleation and how nucleation proceeds determines the crystallization rate and essential properties of the resulting crystal population. Recent results with several proteins indicate that crystals nucleate within preformed mesoscopic protein-rich clusters. The origin of the mesoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Our results resonate with the observations of previous investigators on aggregation phenomena in lysozyme solutions. The importance of driving forces for aggregation at physiological temperatures was emphasized in the work of Vekilov et al [23], where the presence of transient dimers of lysozyme was found. Also, according to Strander et al [10], at the same ionic strength and pH, the presence of short-range attractions and long-range repulsions leads to the formation of dense liquid phases in lysozyme solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results resonate with the observations of previous investigators on aggregation phenomena in lysozyme solutions. The importance of driving forces for aggregation at physiological temperatures was emphasized in the work of Vekilov et al [23], where the presence of transient dimers of lysozyme was found. Also, according to Strander et al [10], at the same ionic strength and pH, the presence of short-range attractions and long-range repulsions leads to the formation of dense liquid phases in lysozyme solutions.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that these aggregates typically had a diameter between 60-200 nm and a fraction of~10 −4 of total soluble protein [21]. The aggregates were commonly thought to be reversible [22], undergoing dynamic molecular exchange with protein in solution [23].…”
Section: Introductionmentioning
confidence: 99%